2016
DOI: 10.2174/0929867323666160405111543
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Copper Homeostasis in Head and Neck Cancer: Review and Meta-Analysis

Abstract: Metals are known for playing essential roles in human physiology. Copper and zinc are trace elements closely dependent on one another and are involved in cell proliferation, growth, gene expression, apoptosis and other processes. Their homeostasis is crucial and tightly controlled by a resourceful system of transporters and transport proteins which deliver copper and zinc ions to their target sites. Abnormal zinc and copper homeostasis can be seen in a number of malignancies and also in head and neck cancer. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…Perturbed metal homeostasis, in particular excess of essential metals, has been associated with carcinogenesis and metastasis [ 33 ]. A meta-analysis revealed that Zinc (Zn 2+ ) and copper (Cu 2+ ) seem to play a particular role in head and neck cancer [ 34 ]. In HT-29 cells it is known that extracellular Zn 2+ supports HT-29 cell growth at 10 μM and inhibits it at 100 μM through a Zn 2+ -sensing receptor that does not seem to alter intracellular Zn 2+ concentrations and involves the ERK pathway [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perturbed metal homeostasis, in particular excess of essential metals, has been associated with carcinogenesis and metastasis [ 33 ]. A meta-analysis revealed that Zinc (Zn 2+ ) and copper (Cu 2+ ) seem to play a particular role in head and neck cancer [ 34 ]. In HT-29 cells it is known that extracellular Zn 2+ supports HT-29 cell growth at 10 μM and inhibits it at 100 μM through a Zn 2+ -sensing receptor that does not seem to alter intracellular Zn 2+ concentrations and involves the ERK pathway [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc in human trace elements correlates with the occurrence and development of malignant tumors, such as rectal cancer, gastric cancer, and breast cancer. Zinc imbalance also affects the occurrence of head and neck cancer [24]. Zinc oxide nanoparticles exert selective cytotoxicity against tumor cells and can serve as an innovative antitumor agent [25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an epidemiological analysis in humans found that chronic or accidental exposure to low doses of dioxins is a potential risk factor for type 2 diabetes (Bertazzi et al, 2001;Wang et al, 2008) and cancer (Leng et al, 2014;Wang et al, 2013). Furthermore, recent findings have demonstrat-ed a relationship between zinc homeostasis disruption and the onset of disease, such as type 2 diabetes (Chu et al, 2017;Yary et al, 2016), Alzheimer's disease (Kawahara et al, 2018;Li and Wang, 2016;Portbury and Adlard, 2015), and cancer (Bafaro et al, 2017;Kolenko et al, 2013;Ressnerova et al, 2016). The precise physiological consequence of disrupted zinc homeostasis by AHR ligands remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc homeostasis is precisely regulated by the balanced actions of zinc-binding proteins, metallothioneins, and zinc transporters (Hara et al, 2017;Hojyo and Fukada, 2016). Given the critical functions of zinc, perturbation of zinc levels would thus be detrimental to cell survival, and several studies have revealed alterations of serum, tissue, and cellular zinc concentrations during the onset of certain diseases, including type 2 diabetes (Yary et al, 2016), Alzheimer's disease (Li and Wang, 2016;Portbury and Adlard, 2015), senile dementia (Kawahara et al, 2014), and cancer (Kolenko et al, 2013;Ressnerova et al, 2016). These findings suggest that zinc homeostasis plays an important role in the onset and progression of disease.…”
Section: Introductionmentioning
confidence: 99%